Uncovering psychological gratifications affecting social media utilization : a multiblock hierarchical analysis - Zolkepli, Izzal Asnira; Kamarulzaman, Yusniza; Kitchen, Philip James (Taylor & Francis, 2018)
The purpose of this study is to examine internet users’ experience and gratifications of social media, which affect the utilization of the medium. The research model was developed in hierarchical multiblock, which consists of three key psychological components–personal, tension release, and social–that are derived from the Uses and Gratifications theoretical perspective. Data were collected through stratified probability sampling of 428 social media users using a web-based questionnaire. They were selected because they spend a significant amount of time on social media sites, at least on Facebook, Twitter, YouTube, LinkedIn, and Instagram. Based on hierarchical multiblock PLS analysis, the results confirmed that social media utilization is affected by three key component psychological factors. All of these factors play a significant part in influencing user attitude toward utilizing social media. The findings are believed to increase understanding, especially for user-experience designers (UXD) concerning venues that can be used for direct targeting in designing social media marketing. The implications and recommendations for future research are discussed.